Chapel of the Nativity of the Lovozersky Sami Churchyard - Mark M. Shakhnovitch; Evgeniy B. Kolivatov (Финно-угорский мир, 2024)
Introduction. The article considers the discovery of a unique object in the Lovozero tundra – the chapel of the Lyavozersky churchyard on Lake Chesynyavr. Monuments of Orthodox Sami culture in the Murmansk region have rarely been studied by specialists The purpose of the study is to introduce into the research circulation the information about existing documents on the history of the chapel, the results of expeditionary work on its survey, and to continue the discussion about the time of construction and the stages of history.